Routledge Handbook of Constitutional Law. - Tushnet, Mark (Taylor and Francis, 2013)
The Routledge Handbook of Constitutional Law is an advanced level reference work which surveys the current state of constitutional law. Featuring new, specially commissioned papers by a range of leading scholars from around the world, it offers a comprehensive overview of the field as well as identifying promising avenues for future research. The book presents the key issues in constitutional law thematically allowing for a truly comparative approach to the subject. It also pays particular attention to constitutional design, identifying and evaluating various solutions to the chall.